Influence of Mode of Hydrothermal Treatment and Precursor State on Phase Formation and Crystallinity of Sodium Titanate - Ervina Putri Wulandari; Zikri Noer; Martha Rianna; Syahrul Humaidi; Muhammad Abduh Akram Agus; Alya Nazwariva; Jihan Murtadha Rambe (Journal of Technomaterial Physics, 2026)
Sodium titanate was synthesized via a sol–gel-assisted hydrothermal method to study phase evolution and crystallinity under different hydrothermal treatment conditions and precursor compositions. Four processing routes were designed: continuous hydrothermal treatment (24 h), interrupted hydrothermal cycles (3 × 8 h), dried-gel hydrothermal treatment, and fresh-gel hydrothermal treatment. X-Ray Diffraction (XRD) was used to analyze the resulting crystal phases and crystallite sizes. Continuous treatment of fresh gel produced monoclinic Na₂Ti₆O₁₃ with small crystallites (12.4 nm), while interrupted processing increased crystallite size to 15.5 nm. Pre-drying of the sol–gel precursor prior to continuous hydrothermal treatment yielded well-defined Na₂Ti₆O₁₃ with enhanced crystallinity and larger crystallites (27.6 nm). In contrast, insufficient precursor stabilization redirected phase evolution toward monoclinic Na₂TiO₃ despite comparable crystallite size. The results demonstrate that the hydrothermal treatment mode primarily governs crystallite growth, whereas the precursor state controls phase selectivity. These findings provide a clear synthesis–structure relationship for tailoring sodium titanate materials.